À sombra das crônicas de Braz José Coelho: palimpsestos de memórias e histórias de uma cidade - (:unkn) unknown (Universidade Federal de Goiás, 2017)
Our proposal is to understand the city in the palimpsest of memories, histories and experiences of Catalão, Goiás, through the narratives of Brás José Coelho, Shadows of Time, in which we problematize the relation between place and memory in historical representations. In addition to the places of memories, we try to perceive what are pointed out in the chronicles: constructed identities, memorable people, disputes of power and privileged memories to the detriment of others. We have as reference theoretical authors that swot concepts of memory, city, places of memory, representation and social practices. We understand culture as a web of meanings, according to Geertz (1978) and the reading of the world as a text to be discovered by the vestiges previously hidden in a palimpsest of memories and histories to be scraped, according to the concept of Pesavento (2004). We conceive the city as a text to be read and deciphered in a teaching and learning essay in the classroom with the chronicles of the book of Coelho (2015), a way that reflects beyond what is seen and perceived than the chronicles point out. Initially we thought about research the life experiences of ordinary people in their places of memories, during the master's degree course and in discussions with the master's advisor; we rethought this form of swot and source of research. Throughout the process, we chose to use the book of Coelho (2015), as a source and object of research. We perceive that the language of the chronicles is accessible to teachers and understandable to students, who can and should use them in history classes to understand an entire historical context of the city of Catalão, the historical characters and their memorable places. We believe that contact with this source and document would awaken in students the desire to know and be part of history, especially that they can construct knowledge by thinking, investigating, questioning and producing something different from what is given. The school is the ideal space for this constructive exercise, having the teacher as a base, who assumes an important role in this didactic process, guiding the swot with the chronicles and the context that approach from memorable places and people.
In the shadow of the chronicles of Braz José Coelho: palimpsestos of memories and stories of a city
Keywords: Cidade; Palimpsesto de memórias e histórias; Identidade e cultura; Ensino de história; City; Palimpsest of memories and stories; Identity and culture; Teaching history; CIENCIAS HUMANAS::EDUCACAO